Unveiling the Leather Industry: By-Products, Production Methods, Equipment, Regulatory & Safety Issues - Kumar, Arpan (Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
This article delves into the multifaceted world of the leather industry, exploring its intricate processes, by-products, production methodologies, and the equipment that shapes this ancient craft. Beginning with an examination of leather by-products, the journey unfolds from rawhide to finished leather, revealing the versatility of materials extracted at each stage. Tanning, the pivotal transformation process, takes center stage, with a focus on both traditional and eco-friendly methods. The article also sheds light on the equipment powering these processes, from tanning drums to finishing machinery. As the leather industry navigates the modern landscape, regulatory issues become paramount. Environmental concerns and chemical usage draw attention from regulatory bodies worldwide, prompting standards to ensure sustainable practices and the reduction of environmental impact. Simultaneously, safety issues within the industry, such as chemical exposure and machinery hazards, are addressed to safeguard the well-being of workers. In essence, this article provides a comprehensive overview of the leather industry, intertwining its rich history with contemporary challenges and innovations. Through understanding the intricate balance between production, regulation, and safety, stakeholders can contribute to shaping a responsible and sustainable future for this timeless craft.Top of Form